Jaminan Perlindungan Korban Tindak Pidana Terorisme: Optimalisasi Lembaga Perlindungan Saksi Korban - Syarifah Citra Meidina; Alphi Sahari; Cakra Arbas (Jurnal Rechten : Riset Hukum dan Hak Asasi Manusia, 2024)
Compensation is a form of indemnification charged to the state as a means of protection for victims of terrorist crimes, aimed at reducing the burden of suffering borne by the victims and/or their families. The compensation provided should be based on the assessment of the damages suffered by the victims. This research uses a normative juridical legal research method to explore the concept of compensation for victims of terrorist crimes and the factors that hinder the provision of compensation to them. The findings obtained from this research are that the concept of compensation for victims of terrorist crimes has been regulated in Law Number 5 of 2018 concerning the Eradication of Terrorism Crimes. The provision of compensation to victims of terrorist crimes is carried out through the institution of LPSK (The Witness and Victim Protection Agency) as mandated by the Law. Factors that influence the provision of compensation to victims of terrorist crimes include internal obstacles, such as delays in the application procedure and the implementation of compensation due to the fact that victims can only obtain their compensation rights based on court verdicts and/or determinations. Additionally, the existing laws may not be oriented towards the interests of the victims, which is deemed contradictory to the purpose of providing legal protection, particularly for victims of terrorist crimes. There are also external obstacles, particularly from the victims themselves, where many victims are unaware of their rights as stipulated in the existing legislation due to a lack of government awareness campaigns regarding the existence of the Victim Protection Law.